Prevention of pelvic floor disorders: international urogynecological association research and development committee opinion. Issue 12 (December 2016) - Bazi, Tony; Takahashi, Satoru; Ismail, Sharif; Bø, Kari; Ruiz-Zapata, Alejandra; Duckett, Jonathan; Kammerer-Doak, Dorothy
Abstract Introduction and hypothesis Pelvic floor disorders (PFD), including urinary incontinence, anal incontinence, and pelvic organ prolapse, are common and have a negative effect on the quality of life of women. Treatment is associated with morbidity and may not be totally satisfactory. Prevention of PFDs, when possible, should be a primary goal. The purpose of this paper is to summarise the current literature and give an evidence-based review of the prevention of PFDs Methods A working subcommittee from the International Urogynecological Association (IUGA) Research and Development (R&D) Committee was formed. An initial document addressing the prevention of PFDs was drafted, based on a review of the English-language literature. After evaluation by the entire IUGA R&D Committee, revisions were made. The final document represents the IUGA R&D Committee Opinion on the prevention of PFDs. Results This R&D Committee Opinion reviews the literature on the prevention of PFDs and summarises the findings with evidence-based recommendations. Conclusions Pelvic floor disorders have a long latency, and may go through periods of remission, thus making causality difficult to confirm. Nevertheless, prevention strategies targeting modifiable risk factors should be incorporated into clinical practice before the absence of symptomatology.